2014
DOI: 10.1063/1.4871937
|View full text |Cite
|
Sign up to set email alerts
|

Zinc vacancy and erbium cluster jointly promote ferromagnetism in erbium-doped ZnO thin film

Abstract: Zn1-xErxO (0.005 ≤ x ≤ 0.04) thin films have been prepared by inductively coupled plasma enhanced physical vapor deposition method. Ferromagnetism, crystal structure, microstructure and photoluminescence properties of the films were characterized. It is found that the chemical valence state of Er is trivalent, and the Er3+ cations play an important role in ferromagnetism. Both saturated magnetization (Ms) and zinc vacancy (VZn) are decreased with the increase of x from 0.005 to 0.03. However, further increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…5 The researchers claimed that the ferromagnetism was due to the intrinsic properties of Er-doped ZnO films and could be interpreted by the bound magnetic polaron model (BMP). At the same time, Chen et al 6 proposed that Zinc vacancy (V Zn ) concentration and the Er clusters can jointly boost the ferromagnetism in the Zn 1−x Er x O thin films. However, there is no clear mechanism for the origin of ferromagnetism in Er-doped ZnO films.…”
Section: Introductionmentioning
confidence: 99%
“…5 The researchers claimed that the ferromagnetism was due to the intrinsic properties of Er-doped ZnO films and could be interpreted by the bound magnetic polaron model (BMP). At the same time, Chen et al 6 proposed that Zinc vacancy (V Zn ) concentration and the Er clusters can jointly boost the ferromagnetism in the Zn 1−x Er x O thin films. However, there is no clear mechanism for the origin of ferromagnetism in Er-doped ZnO films.…”
Section: Introductionmentioning
confidence: 99%
“…2e and S2 corresponds to high resolution Er 4d spectrum of Er:ZnO and the peak at 169 eV represents the presence of Er in trivalent (+3) state in the Er:ZnO. 49,50 Atomic percentage of Er in all the doped samples is evaluated by fitting integrated peak area of individual spectrum and using calibrated atomic sensitivity factor. The doping atomic percentage in all the samples is found to 0.92, 1.85, 2.74, 4.31, and 5.16 % which is in agreement with the targeted doping of 1, 2, 3, 4, and 5 % respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of more Er ions into the ZnO matrix resulted in reduced magnetic ordering due to antiferromagnetic interaction between the Er ions. Chen et al [8] also observed ferromagnetism in inductively coupled plasma enhanced vapor deposition prepared ZnO:Er films. They attributed the ferromagnetism to zinc vacancies and Er-cluster.…”
Section: Introductionmentioning
confidence: 87%
“…The magnetic coupling in Er doped ZnO has been attributed to several factors such as bound magnetic polarons [7], zinc vacancies and Er-clusters [8]. Qi et al [7] reported results from ZnO:Er prepared by RF magnetron sputtering in which they observed ferromagnetic ordering from coupling between the Er ions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation